2021
DOI: 10.1111/ina.12953
|View full text |Cite
|
Sign up to set email alerts
|

Association between prenatal exposure to indoor air pollution and autistic‐like behaviors among preschool children

Abstract: Autism is now seen as being on a spectrum that can range from very mild to severe levels of impairment. 1 Autistic spectrum disorder

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Chen et al (2018b) found a positive and significant relationship between pollution and autism. This is supported by other studies (Ritz et al 2018;Rahman et al 2022a;Raz and Oulhote 2022;Yang et al 2022).…”
Section: Literature Reviewsupporting
confidence: 89%
“…Chen et al (2018b) found a positive and significant relationship between pollution and autism. This is supported by other studies (Ritz et al 2018;Rahman et al 2022a;Raz and Oulhote 2022;Yang et al 2022).…”
Section: Literature Reviewsupporting
confidence: 89%
“…MCS releases not only pyrethrin/pyrethroids [29], but also carbon monoxide (CO), particulate matter (PM) and volatile organic compounds (VOCs) (Figure 1) [30][31][32][33]. Our previous studies showed that prenatal exposure to MCS negatively affects the neurodevelopment of children [34,35]. Additionally, Hisada et al reported a weak positive association between infant development at 18 months of age and prenatal exposure to MCS that contains pyrethroid [36].…”
Section: Introductionmentioning
confidence: 99%
“…Both prenatal and postnatal exposure to air pollution can negatively affect neurological development, lead to poorer cognitive test results, and influence the development of behavioral disorders such as autism spectrum disorders and attention deficit hyperactivity disorder. In particular, the role of pollution in an increased risk of neurodevelopmental disorders, anxiety, and depressive disorders even before birth has been highlighted [ 40 42 ]. As well, there is also a link between household air pollution, low birth weight, and reduced respiratory lung function [ 41 ].…”
Section: Main Textmentioning
confidence: 99%